ANALISIS PENGARUH KOMPONEN JALAN TERHADAP CAPAIAN LAIK FUNGSI JALAN TOL (Studi Kasus: Ruas Jalan Tol Jakarta-Bogor-Ciawi) - Lukmanul Hakim (Universitas Bandar Lampung, 2017)
Jagorawi toll roads have a length of 59 km that is largely untested road-worthy function. To reduce the number of accidents that occur, toll road needs correct and accurate, planning, design, construction, and maintenance of the road is good and right. This study aims to road component effect to road toll function outcome using Structural Equation Modeling (SEM) with the help of software AMOS version 21. Results of the analysis showed that components of the achievements of the achievements worthy function accounted by 69%. The contribution of each component of the road, namely; (1) the geometric path by 29%; (2) the structure of the pavement by 55%; (3) building a complementary road by 33%; (4) the use of road sections by 46%; (5) implementation and management of road engineering by 35%, (6) road equipment related directly to road users by 36%; (7) road equipment that are not directly related to road users by 36%; and (8) road administration by 31 %.